Optimization of Secoisolariciresinol Diglucoside Extraction from Flaxseed (Linum Usitatissimum L.) and Isolation by a Simple Hplc-Uv Method - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2015)
This research was conducted to develop and optimize a methodology to quantify the content of secoisolariciresinol diglucoside (SDG), the main vegetable lignan present in flaxseed. However, at the time of this work, commercial SDG was not available for standard use. Therefore, an effective method to obtain purified SDG from flaxseed was developed using chromatographic techniques. The SDG obtained was of approximately 97% purity. The methanol extraction time, alkali concentrations, and reaction temperature were optimized through a response surface methodology (RSM), and the optimal conditions established for the extractions were 47 degrees C, 58mmolL(-1) sodium methoxide, and 24h. This methodology was then applied to study the variation of SDG content in flaxseed from different cultivars. The SDG content in different varieties of flaxseed ranged from 10.8 to 17.9mgg(-1) in defatted flaxseed flour and from 6.0 to 10.9mgg(-1) in whole flaxseed.